Histogenesis of Conical and Lenticular Papillae in Buffalo Fetus - Verma, Deepanjali; Uppal, Varinder; Bansal, Neelam; Gupta, Anuradha (Indian Journal of Veterinary Anatomy, 2016)
The study was conducted on tongue of 18 buffalo foetii which were divided into three groups after measuring their CVRL viz; Group I-III and their approximate age was calculated. The primitive conical and lenticular papillae were observed in group I at 18.0 cm CVR length on torus linguae. The conical papillae were covered by highly keratinized epithelium. The papillae were better differentiated at 29.0 cm CVRL. In group III at 80.0 cm CVR length, papillae were fully differentiated. Two type of papillae were observed. straight conical and curved conical. The straight conical papillae did not have secondary papillae but the curved one had secondary papillae. In group II at 21.4 cm CVR length, the lenticular papillae were having a broad shape and a connective tissue core The core of the papillae contained mesenchymal cells differentiating into fibroblast, fine collagen fibers and reticular fibers along with large number of blood vessels. The papillae were fully differentiated at 80.0 cm CVR length in group III.